2022
DOI: 10.1101/2022.01.28.478038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curiosity and mesolimbic functional connectivity drive information seeking in real life

Abstract: Curiosity reflects the intrinsic motivation of an individual to seek information in order to close information gaps. Laboratory-based experiments have shown that both curiosity and information seeking are associated with enhanced neural dynamics in the mesolimbic dopaminergic circuit. However, it is unclear whether curiosity and its associated neural dynamics in the dopaminergic circuit drive information seeking in real life. The present study investigated (i) whether curiosity traits predict different charact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…In addition to research on animal exploration, our results align with several initial studies on how curiosity triggers human information-seeking and exploratory behaviour, and are the first in the domain of spatial exploration. These recent studies have shown that curiosity affects information-seeking and exploratory behaviours such as Wikipedia online search (Lydon-Staley et al, 2021) and COVID-19-related information seeking (Eschmann et al, 2022). It has also been shown that curiosity states motivate anticipatory gaze towards the predicted position of upcoming curiosity-relieving information (Baranes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to research on animal exploration, our results align with several initial studies on how curiosity triggers human information-seeking and exploratory behaviour, and are the first in the domain of spatial exploration. These recent studies have shown that curiosity affects information-seeking and exploratory behaviours such as Wikipedia online search (Lydon-Staley et al, 2021) and COVID-19-related information seeking (Eschmann et al, 2022). It has also been shown that curiosity states motivate anticipatory gaze towards the predicted position of upcoming curiosity-relieving information (Baranes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one indication that curiosity might affect spatial exploration comes from findings on how curiosity affects information seeking in the context of knowledge acquisition. For example, it has been found that participants who show generally higher trait levels of curiosity tend to seek more real-life information (e.g., seeking more information about closely related concepts on Wikipedia; Lydon-Staley et al, 2021; informing themselves more often about COVID-19-related news; Eschmann et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Early observations reveal that animals, like humans, acquire information about their world even if that information is of no apparent extrinsic value 1,2 . More recent experiments have addressed the nature of the brain representations of information involved in information seeking decisions [3][4][5][6][7][8][9][10][11][12][13][14][15] , but the question as to how the brain identifies sensory stimuli as informative and computes their intrinsic value remains elusive.…”
Section: Introductionmentioning
confidence: 99%